2017
DOI: 10.18632/oncotarget.14461
|View full text |Cite
|
Sign up to set email alerts
|

Potential roles of microRNAs and ROS in colorectal cancer: diagnostic biomarkers and therapeutic targets

Abstract: As one of the most commonly diagnosed cancers worldwide, colorectal adenocarcinoma often occurs sporadically in individuals aged 50 or above and there is an increase among younger patients under 50. Routine screenings are recommended for this age group to improve early detection. The multifactorial etiology of colorectal cancer consists of both genetic and epigenetic factors. Recently, studies have shown that the development and progression of colorectal cancer can be attributed to aberrant expression of micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 210 publications
(142 reference statements)
0
40
0
Order By: Relevance
“…The development of colorectal cancer is a complex and multi-stage process, characterized by various interactions between environmental carcinogens, genetic modifications and the host immune system (15). Dense infiltration of cytokine-producing immune/inflammatory cells frequently result in the aberrant activation of multiple intracellular signal transduction cascades, ultimately resulting in the uncontrolled growth of transformed cells.…”
Section: Introductionmentioning
confidence: 99%
“…The development of colorectal cancer is a complex and multi-stage process, characterized by various interactions between environmental carcinogens, genetic modifications and the host immune system (15). Dense infiltration of cytokine-producing immune/inflammatory cells frequently result in the aberrant activation of multiple intracellular signal transduction cascades, ultimately resulting in the uncontrolled growth of transformed cells.…”
Section: Introductionmentioning
confidence: 99%
“…Also, treatment of EOC cells with H 2 O 2 caused a dose and time-dependent decrease in miR-29b levels of EOC cells, suggesting miR-29b close involvement in EOC oxidative metabolism. Accumulating studies have revealed that ROS can alter the expression of certain miRNAs [33, 34]. The mechanism underlying ROS-regulated microRNA expression is complicated and poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Both Lin et al9 and Yantiss et al10 found that the miR-203 level in cancerous tissues was significantly higher than that in adjacent normal tissues, and the prognosis was poor if high levels of miR-203 were present. In contrast, Chiang et al11 reported opposite results in 212 clinical specimens of colorectal cancers; they found that the miR-203 level in cancer tissue was lower than in the adjacent areas and 5-year survival rate of patients with lower miR-203 was worse.…”
Section: Introductionmentioning
confidence: 99%